2021
DOI: 10.1186/s12984-021-00954-9
|View full text |Cite
|
Sign up to set email alerts
|

Usability and performance validation of an ultra-lightweight and versatile untethered robotic ankle exoskeleton

Abstract: Background Ankle exoskeletons can improve walking mechanics and energetics, but few untethered devices have demonstrated improved performance and usability across a wide range of users and terrains. Our goal was to design and validate a lightweight untethered ankle exoskeleton that was effective across moderate-to-high intensity ambulation in children through adults with and without walking impairment. Methods Following benchtop validation of custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Tekscan embedded fore-foot pressure sensors (A502) were used to identify stance and swing phase of a gait cycle, and inform the assistive and resistive high-level control strategies (Figure 1a). Additional details of the design can be found in our prior publication (Orekhov et al, 2021).
Figure 1.(a) Pictures of the exoskeleton on a participant with detailed views of the exoskeleton waist and ankle assemblies.
…”
Section: Methodsmentioning
confidence: 99%
“…Tekscan embedded fore-foot pressure sensors (A502) were used to identify stance and swing phase of a gait cycle, and inform the assistive and resistive high-level control strategies (Figure 1a). Additional details of the design can be found in our prior publication (Orekhov et al, 2021).
Figure 1.(a) Pictures of the exoskeleton on a participant with detailed views of the exoskeleton waist and ankle assemblies.
…”
Section: Methodsmentioning
confidence: 99%
“…For example, in ( Lai et al, 2013 ), the authors exploited the strong correlation between the knee angle and hip angular velocity during the swing phase of gait. Other sources of information were the pressure measurements between the thigh muscles and the exoskeleton straps ( Wu et al, 2015 ) for generating a velocity reference profile, or the biological moment of the ankle for generating assistive ( Fang and Lerner, 2021 ; Gasparri et al, 2019 ; Orekhov et al, 2020 , 2021 ) or resistive ( Conner et al, 2020 ) torque profiles.…”
Section: State Of the Artmentioning
confidence: 99%
“…For the majority of the control strategies, the parameter tuning is laborious, as therapists must manually adjust the parameters relying only on subjective feedback from the patients and visual assessments of the gait pattern [6], [7]. A few studies have shown that the process of tuning the control parameters requires the highest amount of time when setting up the device together with donning process [4], [8], [9]. Manual tuning might often lead to a sub-optimal set of parameters, and does not take advantage of the data gathered by the exoskeleton to facilitate the parameter tuning.…”
Section: Introductionmentioning
confidence: 99%